An experimental study on the torrefaction of food waste - Ruwaida, Abdul Rasid; Thye, Mei Chin; Mazni, Ismail (Universiti Malaysia Pahang, 2018)
Municipal solid waste (MSW) in Malaysia is mainly consist of food waste. As food waste is of organic compounds, its improper management may cause serious environmental issues, as it may produce greenhouse gases and polluting leachate [1]. An alternative management of the food waste is through its utilization. However, the main issue in the utilization of food waste is its heterogeneity, whereby the diversified cooking methods as well as food origin emanates different characteristics [2]. Hence, food waste needs to be pre-treated through the torrefaction process, which is a thermochemical method that converts it to biochar at temperature between 200–300°C in an inert environment [3]. The main aim of this work is to evaluate the feasibility of food waste as a potential source of energy through the torrefaction process. The torrefaction of food waste was conducted in a vertical tubular reactor under inert atmosphere. The effects of various torrefaction temperatures (280°C, 300°C and 320°C); residence times (15 minutes, 30 minutes and 60 minutes) and particle sizes (0.5 mm, 1 mm and >1 mm) were investigated.